Locus Minoris Resistentiae: Two Cases of Malignant Metastasis and Review of Literature - Donya Farmand MPH; Michael C. Valdez MD; Leila Moosavi MD; Everardo Cobos MD (SAGE Publishing, 2021)
Locus minoris resistentiae refers to a region of decreased resistance within the body. This occurs from changes to the microenvironment secondary to previous trauma and results in increased vulnerability. As a result, infection, inflammatory processes, and malignancy may localize to this area. In this article, we describe 2 unique cases of malignancy, primary prostate carcinoma and serous carcinoma of the ovary, both of which disseminated to sites of prior trauma. We review the available literature, discuss proposed pathophysiology, and highlight the need for further investigations along with increased clinician awareness.